Representations and public discourse of Chinese family cultures across media platforms. (1st June 2019) - Li, Haili
Leaving Home (2017), a Chinese reality television show focusing on narrating Chinese family stories with an emphasis on Chinese family cultures, became popular among audiences in 2017. Simultaneously, the show triggered large-scale public attention and heated debate on Weibo, a popular Chinese social media site. This commentary analyses how Chinese family cultures have been represented and framed in Leaving Home, and how the show has influenced and shaped public discourse on social media platforms such as Weibo. A content analysis is used to interpret stories in Leaving Home while textual analysis is deployed to analyse the discussion microblogs on the Weibo topic page of Leaving Home. Three types of Chinese family cultures have been foregrounded through examining the narratives of Leaving Home. The analyses of microblogs have demonstrated that Leaving Home's constructions of narratives and emphases on certain topics can affect public discourse on Weibo and shape them in specific directions. Leaving Home has inspired people to interpret its stories and embedded Chinese family cultures and values in their own ways by expressing their opinions on Weibo.